PEMANFAATAN ENERGI ANGIN SEBAGAI ENERGI ALTERNATIF PEMBANGKIT LISTRIK DI NUSA PENIDA DAN DAMPAKNYA TERHADAP LINGKUNGAN - I N. Budiastra; I.A. Dwi Giriantari; Wayan Artawijaya; Cok. Indra Partha (Environmental Research Center (PPLH) of Udayana University, 2009)
The environmental impacts due to technology applications have been an interesting issue for researchers and engineers worldwide. Innovations in development of environmentally friendly technology have been implemented to minimise severe consequences of the impacts, including in electricity generation technology. It has been known that the use of fossil fuel will increase the emission of greenhouse gasses, such as SO2, NO and CO2. A strong regulation for emission of greenhouse gasses has imposed a great extent of efforts in reducing the emitted gases. At present, the electricity need for Penida island is mainly generated using diesel generating system. The use of large amount of diesel oil for electricity generation certainly increases the emitted greenhouse gasses. This paper discusses an alternative technology in wind energy utilisation for electricity generation at Penida Island. The position of Penida island, which is in the ocean front region, yields a high potential use of wind energy for electricity generation. The analysis results show that at the Penida Island, the electricity may be produced with a maximum power of 50kW from a single wind turbine. In order to fulfil the total electrical energy need for the island, it is required to develop hundreds of turbines. Development of this amount of wind turbines certainly produces other related environmental impacts, such as ecological impacts, visual aesthetics and generated noises.